Transcendental-pragmatic justification of Karl-Otto - Filipiak, Magdalena (Hybris, 2017)
The aim of the article is to analyze the discourse ethics postulated by Karl-Otto Apel. This is an original project of the German philosopher, which is a result of linguistic, hermeneutic and pragmatic transformation of transcendental philosophy. In this form the discourse ethics is the embodiment of the idea of the communication turn in philosophy and thus grains the notion of prima philosophia in Apel’s considerations. Transcendental and communication aspect of ethics allows Apel to formulate a postulate of validation of not only specific situational ethical norms but also the principle of ethics itself. The idea is reflected in the postulate of final justification. The dialectics of the ideal and real communication community is, on the one hand, to overcome the aporias of transcendental philosophy and, on the other hand, to retain its fundamental claims. Discourse ethics and co-responsibility are the ultimate response to the threats of the contemporary world, resulting from globalization or technicisation of life.